Les mots de l’écologie : étude lexicométrique d’un corpus bilingue personnalisé (ECOTEXT 2021) - Kaliska, Agnieszka; Gostkowska, Kaja (Studia Romanica Posnaniensia, 2023)
Our goal is to compare the words that are central to the discourses initiated by the most essential environmental protection organizations, both international and local, acting in France and in Poland. Our analysis is carried out in three stages: after briefly presenting some of the computerized corpus analysis methods and equipment we used to collect and process our bilingual corpus named ECOTEXT, we check its specificity and then move on to calculating word frequency and interpreting the frequency lists, starting with the analysis of the most frequent toponyms (e.g. France and Polska) and continuing with the most frequently represented nouns and adjectives. Throughout our analysis we return to the notion of interlinguistic equivalence which, as we shall show, does not turn out to be fully operative in confirming or denying the similarity of two discourses studied.